PROBLEMATIKA PELAKSANAAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Sari, Seli Novia; Hajri, Nurhajri; Andriani, Opi; Wicaksono, Nurzahra Fathiyanabila (Jurnal Pendidikan Vokasi dan Seni, 2023)
The launch of inclusive education in Indonesia with the aim of facilitating the educational needs of children with special needs (ABK) has been widely implemented throughoutIndonesia. Its implementation has found many obstacles or problems experienced by teachers and schools in implementing inclusive education at the elementary school level. The research subjects were teachers who taught at schools providing inclusive education. Data was obtained through an open-ended questionnaire (open questions). The research design used uses an indigeneous psychology approach, part of the scientific approachtradition, where an importand aspect in this approach is the effort to find appropriate methods to uncover phenomena in an investigation. The results of the research show that there are various problems encountered by teachers relate to the readiness of the school itself, such as the lack of teachers competence in dealing with ABK students, problems related to the lack of parental concern for ABK, in addition to the large number of ABK students in one class, and the lack of cooperation from various parties such as the community, experts professionals and government.